Codon usage is less optimized in eukaryotic gene segments encoding intrinsically disordered regions than in those encoding structural domains. Issue 21 (5th October 2016) - Homma, Keiichi; Noguchi, Tamotsu; Fukuchi, Satoshi
Abstract: Codon usage tends to be optimized in highly expressed genes. A plausible explanation for this phenomenon is that translational accuracy is increased in highly expressed genes with infrequent use of rare codons. Besides structural domains (SDs), eukaryotic proteins generally have intrinsically disordered regions (IDRs) that by themselves do not assume unique three-dimensional structures. As IDRs are free from structural constraint, they can probably accommodate more translational errors than SDs can. Thus, codon usage in IDRs is likely to be less optimized than that in SDs. Codon usage in all the genes of seven eukaryotes was examined in terms of both tRNA adaptation index and codon adaptation index. Different amino acid compositions in different protein regions were taken into account in calculating expected adaptation indices, to which observed indices were compared. Codon usage is less optimized in gene regions encoding IDRs than in those corresponding to SDs. The finding does not depend on whether IDRs are located at the N-terminus, in the middle, or at the C-terminus of proteins. Furthermore, the observation remains unchanged in two different algorithms used to predict IDRs in proteins. The result is consistent with the idea that IDRs tolerate more translational errors than SDs.